Construction of 3D interconnected and aligned boron nitride nanosheets structures in phthalonitrile composites with high thermal conductivity - Liu, Xianyuan; Zhou, Heng; Wang, Zilong; Han, Xu; Zhao, Zehua; Guo, Ying; Liu, Wenbin; Wang, Jun; Zhao, Tong (Composites science and technology, 2022)
Effective heat dissipation of polymer-based composites has become a crucial issue in thermal management. Constructing 3D thermal transport frameworks and aligned structures are two effective strategies to improve the thermal conductivity of polymer composites. Herein, boron nitride nanosheets (BNNSs) and phthalonitrile microspheres were assembled to form complex microspheres, and the prepared complex microspheres were hot-pressed to composites with 3D interconnected filler networks. Benefitted from the 3D networks, the composites with 40 vol% BNNSs achieved an ultrahigh thermal conductivity of 4.282 W/mK, which was 16.16 times of pristine phthalonitrile resin (0.265 W/mK). Furthermore, the BNNSs-aligned composites were fabricated via solution mixing and hot pressing, the uniform dispersion and high orientation BNNSs were realized in the resin matrix. Due to the aligned fillers, the in-plane thermal conductivity of the aligned composites was significantly increased to 7.835 W/mK at 40 vol% BNNSs content, which was 29.57 times of pristine phthalonitrile resin. These two simple methods provide new strategies for the design and preparation of composites with high thermal conductivity. [Display omitted] •Developed facile methods to manufacture 3D interconnected BNNSs networks.•Achieve good thermal conductivity while maintaining the excellent comprehensive properties.•Two-dimensional fillers are oriented in the resin matrix by hot pressing.•Thermal conductivity of the isotropic composite is increased to 1616% compared to origin resin.•The in-plane thermal conductivity of the anisotropic composite can reach as high as 7.835 W/mK.